2018
DOI: 10.1590/1678-4766e2018002
|View full text |Cite
|
Sign up to set email alerts
|

Frugivoria por morcegos filostomídeos (Chiroptera, Phyllostomidae) em dois remanescentes urbanos de cerrado em Campo Grande, Mato Grosso do Sul

Abstract: RESUMO Os morcegos filostomídeos são potenciais dispersores de sementes, devido ao seu hábito de forrageio e grande mobilidade, sendo os principais responsáveis pela regeneração de florestas neotropicais. No Mato Grosso do Sul as pesquisas com dieta de morcegos se concentram na região do Pantanal, com poucos trabalhos focados na porção de Cerrado, e somente um em área urbana. O objetivo deste estudo foi analisar a dieta de filostomídeos frugívoros em dois remanescentes urbanos de Cerrado em Campo Grande, Mato … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
2
1
1
Order By: Relevance
“…The dispersion of pioneer plants such as Solanum, Cecropia, and Ficus, shows the importance of bats in the succession processes in different environments (Garcia et al 2000;Muller & Reis 1992). The PERMANOVA results did not indicate differences in the seasonal analyses, but it is important to highlight that other studies revealed higher consumption in rainy periods, when food supply sources greatly increase, especially of Piperaceae species (Passos et al 2003;Mello et al 2004) We found that the richness of fruits consumed by bats was greater than that found in anthropized areas of Cerrado (Martins et al 2014;Torres et al 2018), but it was lower than that recorded in preserved areas of the Atlantic Forest (Laurindo et al 2018). Those results were expected because warmer and humid tropical areas usually present a greater diversity of fleshy fruits (Chen et al 2017).…”
contrasting
confidence: 59%
“…The dispersion of pioneer plants such as Solanum, Cecropia, and Ficus, shows the importance of bats in the succession processes in different environments (Garcia et al 2000;Muller & Reis 1992). The PERMANOVA results did not indicate differences in the seasonal analyses, but it is important to highlight that other studies revealed higher consumption in rainy periods, when food supply sources greatly increase, especially of Piperaceae species (Passos et al 2003;Mello et al 2004) We found that the richness of fruits consumed by bats was greater than that found in anthropized areas of Cerrado (Martins et al 2014;Torres et al 2018), but it was lower than that recorded in preserved areas of the Atlantic Forest (Laurindo et al 2018). Those results were expected because warmer and humid tropical areas usually present a greater diversity of fleshy fruits (Chen et al 2017).…”
contrasting
confidence: 59%
“…We found a change in the direction of the effect of forest cover on the abundance from the 0.5 km to the 1.25 km scale. This suggests that at local scales A. planirostris requires enough forest cover to provide roosting sites and food resources (Mendes et al 2016), whereas at the larger extent the forest cover may reduce its opportunity to exploit available fruit resources in the deforested matrix (Torres et al 2018). Besides, the negative relationship with grass cover at the largest scale, 2 km, suggests a detrimental effect of extremely deforested landscapes on the abundance even for long-distance dispersal bats such as A. planirostris (Meyer et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Morphological traits of plants and frugivores such as fruit and seed sizes and bill gape are important factors defining fruit consumption by animals (Wheelwright 1985). Small fruits are accessible to a wider variety of frugivores and plants with this trait, as well as small seeds, tend to play a central role in communities (Torres et al 2018, Sebastián-González 2017, Vizentin-Bugoni et al 2021. Thus, outplanting of native plants with small fruits (and seeds) may be an interesting strategy to attract and support a greater diversity of frugivores.…”
Section: Functional Matchingmentioning
confidence: 99%